2009
DOI: 10.1111/j.1939-1676.2009.0282.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Acute Phase Protein Concentrations in Dogs with Autoimmune Hemolytic Anemia

Abstract: Background: Serial monitoring of acute phase protein (APP) concentrations in canine autoimmune hemolytic anemia (AIHA) has not been reported.Hypotheses: Acute canine AIHA is accompanied by an acute phase response (APR) characterized by increased C-reactive protein (CRP) and a1-acid glycoprotein (AAG) concentrations and decreased albumin concentrations.Animals: Twenty-seven dogs with AIHA and 11 control dogs. Methods: Prospective, cohort study. CRP, AAG, and albumin concentrations, white blood cell (WBC) count,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 28 publications
4
60
1
2
Order By: Relevance
“…26 Despite the significant association between serum CRP concentrations and odds of death in the present study, results of ROC curve analysis indicated that the discriminative ability of CRP concentration alone in predicting outcome was only moderately accurate. This is in accordance with findings of several oth-er clinical studies 27,[38][39][40] that indicated circulating CRP concentration alone does not correspond to outcome.…”
Section: Discussionsupporting
confidence: 79%
“…26 Despite the significant association between serum CRP concentrations and odds of death in the present study, results of ROC curve analysis indicated that the discriminative ability of CRP concentration alone in predicting outcome was only moderately accurate. This is in accordance with findings of several oth-er clinical studies 27,[38][39][40] that indicated circulating CRP concentration alone does not correspond to outcome.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, interaction of P-selectin with its receptor, PSGL-1, stimulates the production of thrombogenic microparticles from leucocytes (mainly monocytes), which together with platelets and endothelial cells play an important role in thrombogenesis (Ramacciotti et al 2009;Wakefield et al 2009). The presence of an inflammatory response in dogs with IMHA is also evidenced by the activity of chemotaxins, such as monocyte chemoattractant protein-1 and granulocyte macrophage colony-stimulating factor, and acutephase proteins (Tecles et al 2005;Griebsch et al 2009;Mitchell et al 2009;Duffy et al 2010;Yuki et al 2010). …”
Section: Mortality and Thromboembolismmentioning
confidence: 99%
“…Pronounced leucocytosis with a left shift is a common laboratory feature at presentation, or leucocytosis may develop in dogs with leucopenia or normoleukaemia at presentation (Mitchell et al 2009). Monocytosis is present in about 50% of cases (Thompson et al 2004).…”
Section: Complete Blood Countmentioning
confidence: 99%
“…Specific APPs have been reported as value tools in monitoring both infectious diseases, just as CRP and Cp (but not SAA or Hp) in leishmaniasis (Martínez-Subiela et al, 2003) or CRP (but not Hp) in trypanosomiasis (N'dungu et al, 1991), and inflammatory processes, just as SAA in feline acute pancreatitis (associated with remission and recurrence) (Tamamoto et al, 2009) or Hp in bovine respiratory disease (Carter et al, 2002). In other conditions, just as canine hemolytic anemia, the changes in APPs were not useful to monitor the success of specific treatments (Griebsch et al, 2009;Mitchell et al, 2009). On the other side, some prophylactic strategies are carried out in order to prevent the disease.…”
Section: Conclusion: App In the Evaluation Of Prophylaxis And Therapementioning
confidence: 99%